1992
DOI: 10.1021/tx00029a002
|View full text |Cite
|
Sign up to set email alerts
|

Formation, characterization, and toxicity of the glutathione and cysteine conjugates of toxic heptapeptide microcystins

Abstract: Microcystins LR, YR, and RR, cyclic heptapeptide hepatotoxins produced by cyanobacteria, were synthetically converted into glutathione (GSH) and cysteine (Cys) conjugates. Fast atom bombardment mass spectra showed [M + H]+ ions corresponding to GSH and Cys conjugates of microcystins LR, YR, and RR for the obtained compounds. 1H NMR spectral analyses revealed that two singlet signals of olefinic protons of N-methyldehydroalanine (Mdha) in microcystins disappeared in the conjugates, confirming that thiols of GSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
128
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(137 citation statements)
references
References 33 publications
6
128
0
1
Order By: Relevance
“…The glutathione and cysteine conjugates of MCs (MC-GSH and MC-Cys) were firstly synthesized under chemical conditions by Kondo et al (1992) with Frit-FAB liquid chromatographymass spectrometry (LC/MS), and then the resulting conjugates were identified as two metabolites of MCs in vivo in the livers of mouse and rat. Subsequently, MC-LR-GSH was proved to form in various aquatic animals via glutathione Stransferase (GST) in vitro, and it was suggested to be the first step in the detoxification of MCs in aquatic organisms, followed by degradation to the cysteine conjugate (Pflugmacher et al 1998(Pflugmacher et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The glutathione and cysteine conjugates of MCs (MC-GSH and MC-Cys) were firstly synthesized under chemical conditions by Kondo et al (1992) with Frit-FAB liquid chromatographymass spectrometry (LC/MS), and then the resulting conjugates were identified as two metabolites of MCs in vivo in the livers of mouse and rat. Subsequently, MC-LR-GSH was proved to form in various aquatic animals via glutathione Stransferase (GST) in vitro, and it was suggested to be the first step in the detoxification of MCs in aquatic organisms, followed by degradation to the cysteine conjugate (Pflugmacher et al 1998(Pflugmacher et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that glutathione plays an important role in the detoxification of MCs in both mammals and aquatic organisms (Ito et al, 2002;Kondo et al, 1992Kondo et al, , 1996Pflugmacher et al, 1998;Zhang et al, 2009). For example, the glutathione and cysteine conjugates of MCs were identified by Frit-FAB LC/MS in liver samples of mouse and rat treated with MCs (Kondo et al, 1992(Kondo et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical methods such as enzyme-linked immunosorbent assay (ELISA) [18][19][20] and the protein phosphatase inhibition assay [5,21] are useful as screening methods due to their high sensitivity and high throughput, but they often have poor identification ability and the potential for false-positives. Reversedphase high-performance liquid chromatography (HPLC) with UV detection [20], diode array detection [22][23][24][25][26][27] or electrochemical detection [28], LC-mass spectrometry (LC-MS) [29][30][31], capillary electrophoresis (CE) [30], and CE-MS [30] have also been used for the identification and quantification of MCs. The LC method can be much more definitive than bioassays and biochemical methods 0003 since it can provide information for the identification of individual MCs.…”
Section: Introductionmentioning
confidence: 99%